2021
DOI: 10.1088/1742-6596/1832/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive skills of students with high mathematical abilities in solving contextual problems

Abstract: This study aims to explore the metacognitive skills of students with high mathematical abilities in the mathematics education study program at the Faculty of Teacher Training and Education in the University of Tadulako in solving contextual problems. The process of student metacognition is determined by providing a number of contextual problems that must be solved, then explored in stages by thinking aloud and unstructured interviews. It aims to explore students’ metacognitive skills in solving contextual prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…This is because the rubric developed teaches students to think systematically. This is consistent with (Güner & Erbay, 2021;Pathuddin & Bennu, 2021;Sekaryanti et al, 2022;Widodo, 2018) that solving mathematical problems requires systematic thinking. Rubric is a tool for evaluating the teaching and learning process.…”
Section: Assessment Phasesupporting
confidence: 87%
“…This is because the rubric developed teaches students to think systematically. This is consistent with (Güner & Erbay, 2021;Pathuddin & Bennu, 2021;Sekaryanti et al, 2022;Widodo, 2018) that solving mathematical problems requires systematic thinking. Rubric is a tool for evaluating the teaching and learning process.…”
Section: Assessment Phasesupporting
confidence: 87%
“…Metacognition skills play a very important role in solving a non-routine problem that requires a completion process with a single solution but with varied solutions, and many solutions but reasoning and algorithms clearly differentiate them. According to research results [24][25][26] revealed that metacognitive thinking skills affect the ability to solve mathematical problems, so that it effectively increases learning motivation, academic achievement, self efficacy, satisfaction with school and student resilience. Some of the results of previous researchers that became the basis for flipped classroom learning, metacognition and resilience including: [27,28] that the blended learning flipped classroom assisted by the Quipper School application was an option during the COVID-19 pandemic as a solver of metacognition problems that provided many benefits for improving academic achievement, providing interactive, flexible, cost-effective, effective, efficient and resilient experiences for students.…”
Section: Introductionmentioning
confidence: 99%